Drivers Of Purchase Decisions Among Women Consumers In The Home Appliance Sector: A Study In Villupuram District - A.Valarmathi; Dr.N.Jamunarani (Revista Electronica de Veterinaria, 2024)
The present study examines the factors influencing the purchase decisions of women buyers towards home appliances in Villupuram District. With the growing importance of home appliances in modern households, women have emerged as key decision-makers in purchase activities. The study aims to analyse the socio-economic profile, buying behaviour, and the various factors affecting their purchase decisions. The study is based on primary data collected from a sample of respondents using a structured interview schedule. Appropriate statistical tools such as percentage analysis, mean, and factor analysis were employed to analyse the data. The findings reveal that women consumers exhibit a high level of involvement in the decision-making process, with purchase decisions primarily influenced by product-related factors such as quality, durability, technological features, and energy efficiency. In addition, factors such as price, brand reputation, promotional offers, and after-sales service also play a significant role. Women buyers actively engage in information search and comparison of alternatives, often relying on digital platforms, online reviews, and family influence. However, the study also identifies challenges such as high prices, misleading advertisements, and service-related issues. The study concludes that women consumers are well-informed and rational decision-makers, and their behaviour is shaped by a combination of economic, social, and technological factors. The findings provide useful implications for marketers to adopt consumer-centric strategies and improve service quality.